Operation of a 3-phase, 15 K.W. alternator as a synchronous motor - Bixby, Horace E.; Long, Carl C. (My University, 1908)
Introduction: The theory of the synchronous motor and its operating characteristics can be shown very clearly by the use of diagrams. In this way, the variation of the power-factor with the load and with the exciting current is shown.
Citation: Bixby, Horace E. and Long, Carl C. Operation of a 3-phase, 15 K.W. alternator as a synchronous motor. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Engineering; Alternators; Motors; Electricity; Graduating theses; Senior theses; Theses